Impact Evaluation of the Brazilian Social Programs on Family Welfare. - Ana lucia Kassouf; Pedro Oliveira (European Regional Science Association (ERSA), 2014)
Impact Evaluation of the Brazilian Social Programs on Family Welfare Key-words: impact evaluation; cash transfer; public policy; labor supply; child labor; school attendance. This study uses an impact evaluation methodology to analyze the non-contributory pension program BPC on family welfare. The program provides a minimum wage to individuals 65 years-old or more with a per capita family income no greater than 25% of the current minimum wage. It means that the grant is addressed to very poor households and it is well targeted. We also verified that the amount transferred can be considered large when compared to other Brazilian social programs. Therefore, we expect important shifts in life quality of recipients and their families. Primarily we looked for changes in the living arrangements in recipients' households. We found some evidence of increased probability of elders living alone. We considered elders living with the spouse as living alone as well. Some authors argue that old-age pensions could be associated to more independence from the offspring, the spouse, and relatives which could influence their decisions. As our estimates are short run effects, future studies with longitudinal data can pick this effect up if it really exists. When we look at the number of co-residents, we found an increased number of members between 30 and 49 years-old in beneficiaries' households. The results show decreases in the co-residents' labor force participation due to the pension. There is a large decrease in the elderly labor force participation just above the cutoff age and some decrease for adults of more than 30 years of age, but no effect for young adults between 18 and 29 years-old. People with more than 30 years old are very likely to be the adult sons of the beneficiary who may be in charge of the elder. This sort of relationship may be one explanation of this decrease in the labor force participation at that age. Also there could be some intergenerational human capital transfer. Beneficiaries could become more supportive of their grandsons' studies, implying a better school attendance rate of their grandsons and less child labor. We found no effect for school attendance, but we found significant effects for reducing child labor, especially for the younger ones. In this study we could only evaluate the effect upon children co-residing with beneficiaries, but possibly there is a spillover for households of relatives, what lead us to think that the benefit is actually larger than the one we have estimated.
Keywords: 330; impact evaluation; regression discontinuity design; cash transfer; social assistance; public policy; labor supply; child labor; school attendance